Provisioning of Street Lighting based on Ambience Intensity for Smart City - Rajina R Mohamed; Mohamad A Mohamed; Arniyati Ahmad; Muhamad A H Abd Halim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Street lighting is a component that require an efficient energy management system for comprehensive energy savings. It should provide ultimate comfort and safety to road users that contribute to the stability of economy and social of the country as well to the smart city development. Currently many street lighting especially in Malaysia, which is ON in the evening and OFF before the sun sets without taking into consideration the ambient brightness and also the number of vehicles. This condition may increase the use of energy as well as dangerous to motorist. Thus this Ambient Street Lighting project was developed using embedded-based Arduino microcontroller for lighting management based on the circumstances surrounding of the road. A threshold value is set based on a reading of the actual situation in order to test the functionality of the prototype. The Ambient Street Lighting prototype have reacted with success towards surrounding brightness/darkness and number of cars passing by on the street.